Padel: a quantitative study of the shots and movements in the high-performance - Priego Quesada, J. I.; Olaso Melis, J.; Llana Belloch, S.; Pérez Soriano, P.; González Garcia, J. C.; Sanchis Almenara, M. (Journal of Human Sport & Exercise, 2013)
Padel is a sport that has increasing its importance in recent years. Despite this evolution, there is a lack of scientific papers analyzing padel aspects, specifically about the quantification of movements and shots during match. The purpose of this study was to perform quantitative analyses of movements and shots in padel in order to establish the importance of each type. Twenty male professional players were recorded with a video during ten matches and movements (lateral, head-on and backward displacement, split-steps, jump for a smash, and turns pivoting on the right or left foot) and shots (direct and indirect drive, backhand, smash and lob, and direct volley) were identified, quantified and classified. A movement predominance was observed for the lateral displacement followed by head-on displacement and split-step. Direct volley (24.66%) and indirect lob (20.52%) were the most frequent shots, followed by direct smash (17.76%), indirect backhand (14.70%) and indirect drive (14.55%).